1997
DOI: 10.1128/mcb.17.1.309
|View full text |Cite
|
Sign up to set email alerts
|

A 5′ Differentially Methylated Sequence and the 3′-Flanking Region Are Necessary forH19Transgene Imprinting

Abstract: The mouse H19 gene is expressed exclusively from the maternal allele. The imprinted expression of the endogenous gene can be recapitulated in mice by using a 14-kb transgene encompassing 4 kb of 5'-flanking sequence, 8 kb of 3'-flanking sequence, which includes the two endoderm-specific enhancers, and an internally deleted structural gene. We have generated multiple transgenic lines with this 14-kb transgene and found that high-copy-number transgenes most closely follow the imprinted expression of the endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
75
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 41 publications
5
75
0
Order By: Relevance
“…These enhancers are then free to drive the expression of Igf2. Thus, although the DMD is not required for transgenic H19 expression (Pfeifer et al 1996;Elson and Bartolomei 1997), possibly because of the absence of the competing Igf2 gene, it appears to be essential for the optimal and exclusive expression of H19 at the endogenous locus. Second, the maternally derived DMD may form a unique chromatin configuration that promotes transcriptional activity.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These enhancers are then free to drive the expression of Igf2. Thus, although the DMD is not required for transgenic H19 expression (Pfeifer et al 1996;Elson and Bartolomei 1997), possibly because of the absence of the competing Igf2 gene, it appears to be essential for the optimal and exclusive expression of H19 at the endogenous locus. Second, the maternally derived DMD may form a unique chromatin configuration that promotes transcriptional activity.…”
Section: Discussionmentioning
confidence: 98%
“…Absence of this region in a normally imprinted mouse transgene results in parental-independent expression and hypomethylation of the derivative transgene (Elson and Bartolomei 1997), indicating that the DMD is crucial for suppression of a paternally transmitted transgene. This element also has unique properties in Drosophila where it acts as a silencer, despite the absence of DNA methylation in the Drosophila genome (Lyko et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed methylation studies have pinpointed a core region, localized at approximately 2 to 4 kb upstream of the gene, in which CpG dinucleotides are paternally methylated throughout development (38,52,53,57). Furthermore, a study with transgenic mice has suggested that the H19 upstream region is necessary for the imprinted expression of H19 (13). A targeted deletion of the endogenous H19 gene that included 10 kb of upstream sequences resulted in biallelic expression of the 5Ј neighboring insulin-like growth factor 2 (Igf2) and insulin 2 (Ins2) genes.…”
mentioning
confidence: 99%